The Compensation Scheme No One Asked For: The Origins of ACC in New Zealand - McKenzie, Peter (Victoria University of Wellington Law Review, 2003)
The vision laid down in the 1967 Royal Commission Report was radical in scope and quickly became controversial. Led by its Chairman, Sir Owen Woodhouse, the Commission presented a series of connected principles to support that vision, drawing from earlier critiques of the common law system in New Zealand and abroad. This paper explores the legal background in New Zealand prior to the Woodhouse Report and reviews prior movement toward reform, including submissions made by members of the Victoria University Law Faculty. It also describes opposition to the Report from members of the bar and other interest groups, but suggests reasons why the Woodhouse framework was nonetheless able to prevail.